DIRECTED READING THINKING ACTIVITY (DRTA) THROUGH GOOGLE CLASSROOM AND ZOOM-MEETING IN PANDEMIC ERA - Daniarti, Yeni (FKIP, UNIVERSITAS ISLAM SYEKH-YUSUF TANGERANG, 2021)
DRTA is the researchers' choice as a research technique because researchers assume that DRTA techniques are suitable for teaching advanced reading levels for Online classes using Google Classroom (GCR) and Zoom-meeting. The research carried out in the Informatic Engineering Departement of UMT, especially for second-semester students. The research method used a case study as a qualitative method with seven participants. DRTA consisted of three stages (predicting, reading, and proving). Moreover, this technique could do several times, depending on the students' need to ask questions based on what students have read. Then, they might continue with guess and make a summary of the text. This kind of activity would have an impact on the continuation of the reading class. From the students, the researcher found that most of the students like to study English. Sometimes they met difficulties in comprehending the text's meaning. They like reading using DRTA because this material is exciting, and they could understand the text efficiently.